2016
DOI: 10.1002/jcc.24456
|View full text |Cite
|
Sign up to set email alerts
|

The nature of structure and bonding between transition metal and mixed Si‐Ge tetramers: A 20‐electron superatom system

Abstract: A novel superatom species with 20-electron system, Six Gey M(+) (x + y = 4; M = Nb, Ta), was properly proposed. The trigonal bipyramid structures for the studied systems were identified as the putative global minimum by means of the density functional theory calculations. The high chemical stability can be explained by the strong p-d hybridization between transition metal and mixed Si-Ge tetramers, and closed-shell valence electron configuration [1S(2) 1P(6) 2S(2) 1D(10) ]. Meanwhile, the chemical bondings bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 101 publications
0
15
0
Order By: Relevance
“…The HOMOs are all doubly occupied, and the LUMO is higher in energy than the HOMO by 3.27 eV, although the previous investigations have revealed that the HOMO-LUMO gap calculated with the B3LYP functional is more overestimate than that obtained from the other functional (BP86) by ∼1.00 eV. [67][68][69] This indicates that the BSi 11 − anion has a shell-closed electronic structure with a large HOMO-LUMO gap. The HOMO is a Si-Si σ orbital with bonding characters, mainly composed by the 3p orbitals of Si atoms.…”
Section: Bsi 12mentioning
confidence: 90%
“…The HOMOs are all doubly occupied, and the LUMO is higher in energy than the HOMO by 3.27 eV, although the previous investigations have revealed that the HOMO-LUMO gap calculated with the B3LYP functional is more overestimate than that obtained from the other functional (BP86) by ∼1.00 eV. [67][68][69] This indicates that the BSi 11 − anion has a shell-closed electronic structure with a large HOMO-LUMO gap. The HOMO is a Si-Si σ orbital with bonding characters, mainly composed by the 3p orbitals of Si atoms.…”
Section: Bsi 12mentioning
confidence: 90%
“…At the hybrid B3LYP level, the E g value of the complex is predicted to be 2.90 eV, which is calculated from the HOMO (−6.02 eV) and the LUMO (−3.12 eV). A large E g value is strongly related with high‐kinetic stability . This is because that the compounds with the large gaps are energetically unfavorable to add electrons to a high‐lying LUMO or to extract electrons from a low‐lying HOMO, and to form the activated compounds of any potential reaction.…”
Section: Resultsmentioning
confidence: 99%
“…We performed the AdNDP analysis for the RhCD complex, to further elucidate the nature of chemical bonding. As previously reported, this AdNDP method is very efficient to gain insight into the bonding features and has been successfully utilized for the fullerene derivatives, boron, and transition‐metal doped semiconductor clusters . Meanwhile, the AdNDP method is proposed on the basis of the electron pairs in such compounds, and represents the chemical bondings in terms of the forms of n ‐center two‐electron ( n c‐2e) bonds, where n goes from one (lone‐pairs) to maximum number of atoms, defined as 1c‐2e (lone‐pairs), 2c‐2e, 3c‐2e, and so forth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to gain insight into the chemical bonding of the V 15 + cluster, the n -center two-electron ( n c-2e, n going from one (lone-pair) to the maximum number of clusters) bonds were, for the first time, explored using the adaptive natural density partitioning (AdNDP) method proposed by Zubarev and Boldyrev [ 44 ], which has been successfully used to reveal bonding characteristics not only for organic aromatic molecules [ 48 , 49 ], but also for boron [ 50 , 51 ] and transition-metal doping clusters [ 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%